Proceso de creación del portal de noticias digital Lucidez.pe - Ramirez de la Torre, Gonzalo Mateo (2021)
This professional sufficiency thesis describes the process of constitution and development of the online newspaper Lucidez.pe. In addition to explaining how the portal was consolidated in the informational digital media market, the report offers the author’s perspective, who founded the newspaper in 2014 and directed it between 2015 and 2018. Through this, it explores the role played by the platform in public opinion and political discussion. From this point of view, and consulting the opinion of experts and reviewing the readership statistics obtained in five years of existence, the strengths and weaknesses of the process are analyzed, as well as the opportunities and future threats of Lucidez.pe might face.